Social class, parents' education and dental caries in 3- to 5-year-old children - Chosack, A.; Cleaton-Jones, P.; Matejka, J.; et al (My University, 1990)
The caries prevalence of 1273-, 4- and 5-y-old white children was determined with mirror and probe under natural light at mother and child clinics. The social class of the family, the educational level of the mother and that of the father were determined from a questionnaire filled in by the accompanying adult at the time of examination. Both social class and parent's education had a statistically significant influence on the caries prevalence: those in the lower social classes and with parents without tertiary education had a much higher prevalence of caries
KIM
Keywords: Dental Caries; Educational Status; Social Class; South Africa